Financial Literacy Concepts Appropriate for Early Childhood: A Field Study from the Perspective of Kindergarten Teachers - Aldossary, Norah Saleh Abdullah; Etman, Ali Abd Eltawab Mohamed; Omar, Sahar Mansour Sayed (Journal of Posthumanism, 2025)
The current study aims to identify appropriate economic and financial concepts for kindergarten children from the perspective of kindergarten teachers. The study sample consisted of 109 kindergarten teachers from the Najran community. A descriptive approach and a teacher questionnaire were used. The study concluded that teachers possess the foundations for developing children's economic concepts and focus on some important concepts, such as rational consumption, the purchasing power of money, valuing work, negotiation, saving, and investment. The study demonstrated the teachers' familiarity with these essential concepts and their ability to develop them appropriately for children, relying on educational activities and programs appropriate for children at this early age.